2005
DOI: 10.1152/ajprenal.00207.2004
|View full text |Cite
|
Sign up to set email alerts
|

Renal medullary gene expression in aquaporin-1 null mice

Abstract: Mice that lack the aquaporin-1 gene (AQP1) lack a functional countercurrent multiplier mechanism, fail to concentrate the inner medullary (IM) interstitium, and present with a urinary concentrating defect. In this study, we use DNA microarrays to identify the gene expression profile of the IM of AQP1 null mice and corresponding changes in gene expression resulting from a loss of a hypertonic medullary interstitium. An ANOVA analysis model, CARMA, was used to isolate the knockout effect while taking into accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…Total RNA was isolated from the inner medulla of control (samples C1, C2, C3) and water-restricted mice (samples E1, E2, and E3) for microarray analysis of gene expression using our previously published methods (21). Total RNA from each sample was then amplified before being labeled in the cDNA reaction and each sample from an individual mouse was hybridized to an array four times (see MIAME document, supplemental data).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Total RNA was isolated from the inner medulla of control (samples C1, C2, C3) and water-restricted mice (samples E1, E2, and E3) for microarray analysis of gene expression using our previously published methods (21). Total RNA from each sample was then amplified before being labeled in the cDNA reaction and each sample from an individual mouse was hybridized to an array four times (see MIAME document, supplemental data).…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA from each sample was then amplified before being labeled in the cDNA reaction and each sample from an individual mouse was hybridized to an array four times (see MIAME document, supplemental data). Data were analyzed and transformed as previously described (21). The ANOVA was performed on a gene by gene basis and was limited to genes that were measured confidently on a minimum of three of the four hybridizations, for at least one sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, it has been generally assumed until recently that the expression of aldolase B in the kidney is restricted to the cortex and more precisely to the proximal tubules (44 -46). However, recent studies revealed that aldolase B is also expressed in the renal medulla (47). Most interestingly, Lu et al (25) indicated that in mouse kidney, aldolase B protein is detected in the cytoplasm of the thick ascending limb and in the Bowman capsule.…”
Section: Nkcc2 Expression In Mammalianmentioning
confidence: 99%